1999
DOI: 10.1017/s1350482799001127
|View full text |Cite
|
Sign up to set email alerts
|

How significant is the usual assumption of neutral stability in evapotranspiration estimating models?

Abstract: The significance of the atmospheric stability approach in models for estimating evapotranspiration is studied by considering the errors encountered when simply adopting neutral instead of actual stability conditions. Maize, cotton and wheat crops grown in 10 hectare fields (central Greece) were used to estimate actual and maximum evapotranspiration for both stability considerations, employing a model based on the equations of Shuttleworth & Wallace (1985). The required meteorological data were recorded in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Increased movement of the air around a plant will result in a higher transpiration rate (USGS, 2007). Andranistakis et al (1999) studied the significance of the atmospheric stability approach in models for estimating ET and concluded that the actual stability conditions have to be taken into account in the case of estimating the daily ET. Fernandez et al (1996) studied the importance of vegetation properties in estimating the ET in semi-arid areas.…”
Section: Introductionmentioning
confidence: 99%
“…Increased movement of the air around a plant will result in a higher transpiration rate (USGS, 2007). Andranistakis et al (1999) studied the significance of the atmospheric stability approach in models for estimating ET and concluded that the actual stability conditions have to be taken into account in the case of estimating the daily ET. Fernandez et al (1996) studied the importance of vegetation properties in estimating the ET in semi-arid areas.…”
Section: Introductionmentioning
confidence: 99%